A Multicenter Analysis of Immune Checkpoint Inhibitors as Adjuvant Therapy Following Treatment of Isolated Brain Metastasis. (8th December 2020) - Randall Patrinely, J.; Funck‐Brentano, Elisa; Nguyen, Khang; Rapisuwon, Suthee; Salem, Joe‐Elie; Gibney, Geoffrey T.; Carlino, Matteo; Johnson, Douglas B.
Abstract: Background: The objective of this work was to characterize outcomes of patients with isolated brain metastases managed with local therapy followed by immune checkpoint inhibitor (ICI) therapy. Materials and Methods: Patients from four medical centers were included if they presented with isolated brain metastases treated with local therapy and received adjuvant treatment with ICIs. Results: Eleven patients with median size of largest brain metastasis of 3.9 cm, treated with surgical resection ( n = 8) and/or stereotactic radiosurgery (SRS; n = 6), were included. Ipilimumab/nivolumab was the adjuvant ICI used in four patients, of whom one recurred (25%) and none died, compared with three of seven (43%) who recurred and two of seven (29%) who died following adjuvant treatment with ICI monotherapy. All recurrences were intracranial. Conclusion: Patients with isolated brain metastases treated with surgery or SRS appeared to benefit from adjuvant ICI therapy, particularly with combination therapy. Recurrences in this setting appear to largely occur intracranially. Abstract : Optimal management for patients with isolated resected brain metastases remains unclear. This article describes a series of patients presenting with isolated brain metastases managed with definitive local therapy (surgery and/or stereotactic radiosurgery) followed by immune checkpoint inhibitor (ICI) treatment.